An optimized analysis of 2‐acetyl‐1‐pyrroline content diversity in the core collection of aromatic rice germplasm (Oryza sativa L.). Issue 4 (21st June 2019) - Xie, Li‐Hong; Tang, Shao‐Qing; Wei, Xiang‐Jin; Jiao, Gui‐Ai; Sheng, Zhong‐Hua; Hu, Pei‐Song
Abstract: Background and objectives: Aromatic rice constitutes a small but a special group of rice varieties, considered as the best in quality. A headspace solid‐phase micro‐extraction (HS‐SPME) method, combined with a gas chromatography–mass spectrometry (GC‐MS) assay, was developed to enable the rapid, simple, and reliable quantification of 2‐acetyl‐1‐pyrroline (2AP) in rice. Findings: The most effective release of 2AP was obtained using a divinylbenzene/carboxen/polydimethylsiloxane (DVB/CAR/PDMS) fiber and extracting brown flour or single whole brown grain at 80°C for 30 min. By the optimized protocol, the limit of detection (LOD) and limit of quantification (LOQ) for 2AP was 1.0 µg/kg of 2AP and 4.0 µg/kg of brown rice flour, respectively. The reproducibility and interday repeatability were <5.00% RSD ( n = 10) and 12.5% RSD ( n = 27), respectively. A good linearity was observed from 5 to 80 ng with a good correlation coefficient ( R 2 ) value of 0.9892. When the method was applied to a collection of aromatic rice germplasm, the 2AP content in 34 entries appeared to be below the limit of detection. The mean 2AP content in the set was 0.45 mg/kg, and the range was from undetectable to 2.73 mg/kg. Most entries contained 0.09–0.46 mg/kg 2AP. Conclusions: A rapid 2AP assay of brown flour or single brown whole grain, based on HS‐SPME combined with GC‐MS, was shown to generate reproducible and reliable outputs. When applied to a set of 228 aromatic rice entries, it was able to reveal the existence of substantial variation for 2AP content. Significance and novelty: The results of this study produced an accurate, rapid, and highly reproducible assay, which are suitable for the screening of large numbers of samples and the helping of aromatic rice breeding.